Comprehensive analysis of predictive factors for rapid angiographic stenotic progression and restenosis risk in coronary artery disease patients underwent percutaneous coronary intervention with drug‐eluting stents implantation. Issue 2 (17th September 2018) - Wu, Yanqiang; Fu, Xianghua
Abstract : Background: This study aimed to explore the correlation of baseline, procedural, and postprocedure characteristics with the risk of rapid angiographic stenotic progression (RASP) and restenosis in coronary artery disease (CAD) patients after percutaneous coronary intervention (PCI) with drug‐eluting stents implantation. Methods: Two hundred fourteen CAD patients underwent PCI with drug‐eluting stents implantation were consecutively enrolled. Baseline, procedural, and postprocedure characteristics of patients were collected for analysis. Coronary angiography was performed to evaluate coronary stenosis before PCI and at 12 months after PCI. RASP of nontarget lesions and restenosis of stent‐implanted target lesions were then assessed. Results: 37.8% CAD patients occurred RASP at 12 months after PCI and compared to non‐RASP group, RASP group presented with increased diabetes mellitus (DM) complication, higher concentration of serum uric acid (SUA), cardiac troponin I, N‐terminal probrain natriuretic peptide, and high sensitive C‐reactive protein (hs‐CRP) as well as elevated occurrence of multivessel artery lesions. In addition, DM, SUA, hs‐CRP, and multivessel artery lesions independently predicted high RASP risk. For restenosis, 21.0% patients occurred restenosis at 12 months after PCI, and patients in restenosis group presented with increased hypertension and DM occurrence, higher concentrations of SUA, LDL‐C, and hs‐CRP, as well as longer target lesion and length of stent in surgery compared to nonrestenosis group. Also, DM, SUA, LDL‐C, hs‐CRP, and length of target lesion independently predicted increased restenosis risk. Conclusion: Diabetes mellitus, SUA, and hs‐CRP are potential predictive factors for increased risk of both RASP and restenosis in CAD patients underwent PCI and drug‐eluting stents implantation.